The Effect Of Colouring Agent (Fe2O3) On The Physical And Mechanical Properties Of Glass Ceramic Produced By Recycling Waste Glass - Nur Farizan, Ayoob (2013)
Large volume of waste glass (e.g. bottles, jars and windowpanes) is being generated and discarded daily and this is likely to increase considerably in the future. Thus, efforts to reduce such wastes by recycling which give benefit to the economy and sustaining the environment are needed. In this research, waste glass is utilized as raw material for the production of glass ceramic material (GCM) via sinter crystallization route. Basically, the main aspiration is to maximise the utilization of waste glass amount; as to enhance recycling effort. Two types of waste soda lime glass (SLG) that are non-coloured and green coloured is utilised as the main raw material during the batch formulation. Optimization of processing parameters (batch composition and sintering temperature) is carried out as an attempt to produce high quality sintered GCM. The glass were milled and sieved to < 75 μm and mixed with ball clay. Similar ball clay content is add into different type of waste glass according to the ratio of SLG to ball clay of 95: 05 wt. %, 90: 10 wt. % and 85 :15 wt. %. The batch mixtures were then uniaxial pressed and sintered at 800 ºC, 825 ºC and 850 ºC with holding time of one hour. The GCM properties were then compared between those produced using non-coloured and green coloured SLG in order to evaluate the effect of colouring agent (Fe2O3) on the GCM produced. It was observed that the colour of the GCM produced from non-coloured SLG is brownish while GCM produced from green coloured SLG is slightly pale green. The main crystalline phase in both GCM (identified using X-ray diffraction analysis) is wollastonite (CaSiO3). Microstructure analysis conducted using scanning electron microscope (SEM) reveals the presence of needle-like crystals of wollastonite indicating that crystallization take place during the sintering. The optimum properties of non-coloured SLG is produced with smaller ball clay content (10 wt. %) compared to green coloured SLG (15 wt. %). The physical properties (determined thru ASTM C373) of the optimized GCM produced from non-coloured SLG and green coloured SLG are 0.69 % of porosity, 1.92 g/cm3 of bulk density, 0.36 % of water absorption; and 1.96 % of porosity, 2.69 g/cm3 of bulk density, 0.73 % of water absorption; respectively. Meanwhile, the optimized mechanical properties of Vickers microhardness and modulus of rupture (determine thru ISO 10545-4) is (580 HV0.5, 39 MPa) for non-coloured SLG and (510 HV0.5, 44 MPa) for green coloured SLG. In conclusion, there were not extremely difference between non-coloured and green coloured SLG being utilized in GCM. The used of both glasses as raw material is able to positively produced good physical and mechanical properties of GCM as results of a modification of their sintering behaviour.